Consequence of induced magnetic field on peristaltic motion of a Carreau nanofluid in a tapered asymmetric channel. Issue 9 (4th September 2017) - Kothandapani, M.; Pushparaj, V.
Abstract : Purpose: This paper aims to investigate the consequence of the combined impacts of an induced magnetic field and thermal radiation on peristaltic transport of a Carreau nanofluid in a vertical tapered asymmetric channel. The model applied for the nanofluid comprises the effects of Brownian motion and thermophoresis. Design/methodology/approach: The governing equations have been simplified under the widespread assumption of long-wavelength and low-Reynolds number approximations. The reduced coupled nonlinear equations of momentum and magnetic force function have also been solved analytically using the regular perturbation method. Findings: The physical features of emerging parameters have been discussed by drawing the graphs of velocity, temperature, nanoparticle concentration profile, magnetic force function, current density, heat transfer coefficient and stream function. It has been realized that the magnetic force function is increased with the increase of Hartmann number, magnetic Reynolds number and mean flow rate. Originality/value: It may be first paper in which the effect of induced magnetic field on peristaltic flow of non-Newtonian nanofluid in a tapered asymmetric channel has been studied.